PENGEMBANGAN PROGRAM KECAKAPAN HIDUP (LIFE SKILLS) UNTUK PEMBERDAYAAN MASYARAKAT SEKITAR PESANTREN - Pudji Muljono; Dian Noor Tamzis Hanafi (Puslitbangkesos Kementerian Sosial RI, 2009)
The Improvement of Life Skills Program for Community Empowerment of Surrounding Islamic Boarding School.Â As the effect of economic crisis in 1998 and facing global economic crisis situation since 2008, Indonesia has to overcome various social problems such as unemployment, the increasing number of drop-out students, and the increasing rate of the poverty. This phenomenon drives the Department of National Education (DNE) to establish the Life Skills Program involving the society. But, there are different concepts and implementation about this program between World Health Organization (WHO) and DNE. The government policy give opportunity for the society to actively engage in education sector is responded by the community of Village of Sukosono, District of Kedung, Regency of Jepara by establishing Community Learning Center (CLC)